A longitudinal study of four-year changes in physical fitness among university students before and after COVID-19: 2019–2022 - Liangru Guo; Liang Jiang; Huizhi Huang (PLoS ONE, 2025)
Background Physical fitness is a key indicator of health in youth and was significantly affected by the COVID-19 pandemic. However, longitudinal studies tracking pandemic-related fitness changes over four years in university students, particularly those enrolled before the pandemic, remain scarce. Understanding these long-term effects on body composition, fitness, and obesity prevalence—with attention to sex differences—is essential. Methods This four-year cohort study included 4,413 Chinese university students (27% male, 73% female). From 2019 to 2022, participants underwent annual physical fitness assessments, measuring height, weight, vital capacity, long-jump, sit-reach, 50-m run, and sex-specific tests (1,000-m run/pull-ups for males; 800-m run/sit-ups for females). Statistical analyses included one-way ANOVA, LSD tests, and Chi-squared tests. Results Weight and obesity rates increased significantly, with male obesity rising from 6.97% to 11.6% and female obesity from 1.9% to 3.45%. Overweight prevalence also grew slightly. Vital capacity peaked in 2021 but declined sharply in 2022 (males: 4,114.16 mL to 3,934.31 mL; females: 3,314.69 mL to 2,957.8 mL). Long-jump and sit-reach performance declined, and cardiorespiratory endurance (1,000-m/800-m runs) worsened post-2020. Female students improved in 50-m runs and sit-ups, while males showed no significant changes in 50-m runs or pull-ups. Conclusions The pandemic significantly impacted university students’ physical fitness over four years, exacerbating obesity risks and declining cardiorespiratory endurance, particularly in males. Schools should prioritize BMI management, obesity prevention, and targeted fitness interventions—emphasizing agility, strength, and late-stage cardiorespiratory training—to mitigate long-term health consequences.